PENGARUH KONSUMSI ANIME DAN MANGA TERHADAP PEMBELAJARAN BUDAYA DAN BAHASA JEPANG - Lufi Wahidati; Mery Kharismawati (IZUMI, 2018)
(Title: The Effect of Anime and Manga Consumption on Japanese Language and Culture Learning) This research was conducted to look at how far anime and manga effect Japanese language learning among the students of the Japanese Program in the Vocational College of Universitas Gadjah Mada. The data were collected via a question form. The question form was distributed to 2nd year and 3rd year Japanese students in May 2017. The questions in the questionnaire include the Japanese language learning motivation, the level of interest in Japanese anime and manga, frequency of consuming anime/manga, as well as the effect on the Japanese language learning by consuming the products. From the data obtained, things can be concluded as follows: 1) most of the students stated that the first time they knew Japanese was through anime/manga; 2) watching anime can support students’ Japanese learning, especially for vocabulary enrichment, listening exercises, and understanding the context of the use of Japanese words or expressions; and 3) most of the students experienced a change of perceptions about Japanese language and culture after learning Japanese in the university. However, the language used in the anime contains stereotypical elements (known as role language or yakuwarigo) and therefore yakuwarigo and sociological context in Japanese should be introduced to the students. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor